Non-Fumigant Treatments and Their Combinations Affect Soil Pathogens and Strawberry Performance in Southern California. (30th November 2016) - Daugovish, Oleg; Howell, Anna; Fennimore, Steven; Koike, Steven; Gordon, Thomas; Subbarao, Krishna
ABSTRACT: Finding effective non-fumigant solutions to soil disinfestation is an international priority for sustainable strawberry production. In these studies at Ventura, California, combinations of steam, solarization, and mustard meal were evaluated to manage troublesome soil-borne pathogens: Macrophomia phaseolina and Fusarium oxysporum . Treatments containing steam and solarization reduced levels of these pathogens in soil 70–96% compared to untreated soil and had lower rates of late season pathogen-related plant mortality. All treatments improved plant canopy growth and fruit production of 'San Andreas' strawberry 58% to 83% compared to untreated control. Even though these treatments did not eradicate pathogen spores and sclerotia in soil, they enhanced early and whole season fruit production and when feasible can be applied in non-fumigated and organic strawberry fields to help sustain production.